(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2007)
A number of anti-inflammatory medical preparations were investigated by their action on free radical processes in lipids. It has been shown that all chemical products have different antioxidant properties and can suppress the intense of chemiluminescence.